Movement Disorders in Children: An Observational Study in a Tertiary Care Center in North India - Pandey, Chandra Shekhar; Kumar, Rashmi; Malhotra, Hardeep Singh; Kohli, Neera; Kumar, Chandrakanta; Verma, Sanjeev Kumar (Journal of Pediatric Neurology, 2020)
Movement disorders (MDs) are disorders of pathological movements that cannot be fully initiated, modulated, or interrupted voluntarily. Spectrum and etiology of MDs are likely to vary with geographical location, but there are few studies on pediatric MDs from India, and severity of the disease is not well documented. Response to treatment of MDs is often unpredictable. Objective of the study was to describe the relative prevalence, types, severity, etiology, and response to treatment of pediatric MDs as seen at a public teaching hospital in northern India. Over a period of 1 year, consecutive children with MDs seen in outpatient department (OPD) or wards were enrolled, after excluding cerebral palsy and musculoskeletal disorders. Detailed history, examination, treatment, and outcome were recorded. Severity was rated according to Battini's scale at initial contact and each follow-up. Neuroimaging and relevant investigations were done for etiology. Serial 2-minute video recordings were obtained. Out of 93 patients enrolled, the most common MDs were dystonia (24.7%), tremors (22.4%), ataxia (19.6%), and chorea (12.9%). Tics, hemiballismus, and myoclonus were also seen and 4% could not be classified. Mixed MDs were seen in 9.7%. Etiologies of MDs were infectious (acute encephalitis syndrome, tuberculous meningitis, subacute sclerosing panencephalitis, and rheumatic chorea) or nutritional (infantile tremor syndrome) in 46%. Genetic neurodegenerations accounted for a significant proportion (15.1%). Improvement occurred in majority (63.4%) of patients. Etiology of MDs was largely specific to this part of the world, related to infectious and nutrition causes. In the absence of complex genetic investigations, many cases were left with unknown etiology.
Keywords: movement disorders; children; India